Effective Leadership In The Digital Age: Challenges And Strategies In Education - lestari, widia dwi; Pertiwi, Santhi; Rizki, Aprilia; Sari, Eliana; Karnati, Neti (Annpublisher, 2024)
This study aims to describe effective leadership in the digital era to discover the challenges and strategies. The method used is literature study by reading, writing, analyzing, and summarizing. The data sources used are literature sources, namely books and journals related to research topics. The data analysis technique uses content analysis. Content analysis is used to research the most relevant, relevant, and quite relevant literature. Then, a study was carried out by looking at the year of publication from the most up-to-date, up-to-date, to not up-to-date but having substance related to this research. Then, the researcher reads the abstract, which will then be researched and recorded in detail by the researcher. This research results in effective leadership oriented towards data-based decision-making and wisdom is a solution for leadership in the digital era. The strategies formulated are (1) strengthening the quality of human resources, (2) improving facilities and infrastructure, (3) making decisions based on qualitative and quantitative data, and (4) acting wisely in facing challenges. Effective leadership is one of the solutions of leadership types in answering challenges in the digital era.